Psychopathology of Time in Brain Disease and Schizophrenia - John Cutting; Herta Silzer (Behavioural Neurology)
The literature on disturbance of time-sense in brain disease and schizophrenia is reviewed and the subjective experience of altered time-sense reported by 45 out of 350 personally interviewed schizophrenics is analyzed. A review of the literature on the effect of brain damage revealed that some phenomena (déjà vu, reduplication of time, altered tempo to events) were linked with right hemisphere dysfunction, one phenomenon (incorrect sequencing of events) was linked with left anterior brain damage, and others (disrupted “biological clock”, disturbed serise of rate of flow of current or past events) could arise from subcortical as well as focal cortical damage. The sparse literature on disturbed time-sense in schizophrenia suggested that there was a shared psychopathology in this respect with right hemisphere dysfunction. The phenomena encountered in the 45 schizophrenics are described and classified.